VIRTUAL PRIVATE NETWORK (VPN) PADA SISTEM OPERASI WINDOWS SERVER SEBAGAI SISTEM PENGIRIMAN DATA PERUSAHAAN MELALUI JARINGAN PUBLIK (STUDI KASUS: JARINGAN TOMATO DIGITAL PRINTING) - Napianto, Riduwan; Utami, Emma; Sudarmawan, Sudarmawan (Universitas Respati Yogyakarta, 2012)
Tomato Digital Printing Company is a company engaged in the display promo has started on the development of sales techniques and information with menerimaan orders or orders from customers who are served at the customer's premises is located. Development is done to improve service to customers and to face the competition in this business.Basic problem, how companies can transmit data or files from the customer premises to the office or otherwise be safely, effectively and efficiently through the public network or the internet.To overcome this problem researchers implement a VPN with Hamachi as a method of data delivery solutions for enterprises and be the right choice for the company.Â Keywords: Internet, VPN, Hamachi